The future of (almost) everything the global changes that will affect every business and all of our lives - Dixon, Patrick (London Profile Books, 2015)
Patrick Dixon looks at how the future will be Fast, Urban, Tribal, Universal, Radical and Ethical - a future of boom and bust and great economic change as the emerging markets grow up; a future of great advances in medicine and also greater threats from viral epidemics; a future of political shocks and greater conflicts; a future in which people will strive for more privacy and businesses will change the way they relate to their staff and their customers; a future in which there will be driverless cars and solar power generated in the desert will power cities thousands of miles away.
Includes index.
Keywords: Social change